2016
DOI: 10.1007/jhep08(2016)171
|View full text |Cite
|
Sign up to set email alerts
|

Initial conditions for hydrodynamics from weakly coupled pre-equilibrium evolution

Abstract: We use effective kinetic theory, accurate at weak coupling, to simulate the preequilibrium evolution of transverse energy and flow perturbations in heavy-ion collisions. We provide a Green function which propagates the initial perturbations to the energymomentum tensor at a time when hydrodynamics becomes applicable. With this map, the complete pre-thermal evolution from saturated nuclei to hydrodynamics can be modelled in a perturbatively controlled way.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(121 citation statements)
references
References 40 publications
4
117
0
Order By: Relevance
“…2 by introducing various sources of event-by-event fluctuations such as number and positions of participant nucleons, their interaction strength, etc. However, it is important to emphasize in this context that the pre-equilibrium phase also modifies the statistics of fluctuations, such that for the long wavelength perturbations [21,22] δs hydro s hydro = 2 3…”
Section: ] and Ads/cftmentioning
confidence: 99%
“…2 by introducing various sources of event-by-event fluctuations such as number and positions of participant nucleons, their interaction strength, etc. However, it is important to emphasize in this context that the pre-equilibrium phase also modifies the statistics of fluctuations, such that for the long wavelength perturbations [21,22] δs hydro s hydro = 2 3…”
Section: ] and Ads/cftmentioning
confidence: 99%
“…In support of its potential phenomenological relevance, this perturbative approach-if supplemented with realistic values of the coupling constantleads to short hydrodynamization timescales [55] comparable to those obtained from non-perturbative strong coupling techniques [58][59][60][61][62] and favored in phenomenological models. This approach has been extended to 2+1 dimensional solutions [63] which form the foundation of tools that can be used to match the out-of-equilibrium initial stage models to a hydrodynamic stage in nucleusnucleus collisions [64,65]. In these solutions the transverse translational symmetry is, however, broken only by small linear perturbations limiting their use in the study of small systems which potentially do not reach the fluiddynamic regime before disintegrating due to transverse expansion.…”
Section: Introductionmentioning
confidence: 99%
“…We will find that the early stage is quite efficient in producing photons, therefore our results support the absence of a dark age in RHICs. Photons from a thermalizing early stage have been also studied very recently in [14], where the bottom-up thermalization scenario of [31] has been adopted; classical-statistical simulations have shown that bottom-up is the right thermalization scenario [32,33] and it extrapolates to finite couplings quite well [34,35]. Our results agree with the importance of the early stage photons production in RHICs already highlighted in [14]; with respect to [14], our main novelty is to implement photon production by a code based on relativistic transport theory and set up to follow the dynamical evolution of the system produced in RHICs, from the early stage up to the freezout, thus allowing a more direct link to the observables of RHICs.…”
Section: Introductionmentioning
confidence: 99%